Pengaruh Penambahan Polimer Poliakrilamida Terhadap Plastisitas dan Daya Dukung Tanah Lokal Sebagai Material Timbunan - Anna Dewi; Dewi Amalia; Lindung Zalbuin Mase; Ery Radya Juarti; Apip Pudin (Borneo Engineering : Jurnal Teknik Sipil, 2022)
The difficulty of obtaining embankment material as a road foundation is one of the problems in the construction of road infrastructure. Furthermore, soil with a low bearing capacity value can damage the road structure. Soil improvement with local soil stabilization is an effective solution to reduce construction costs in the procurement of embankment material. However, the soil quality in an area varies and does not always meet the requirements of the embankment material. From this, it can be concluded that there is need for soil improvement, one of which is soil stabilization with polymer. In this study, Cisasawi soil material was mixed with synthetic polymer polyacrylamide (PAM) in concentrations ranging from 0,2%, 0,4%, 0,6%, 0,8%, and 1%, and then atterberg limits and CBR laboratory were determined. At the end,  an observations was made to the effect of adding PAM for plasticity and bearing capacity of soil. The results of the tests show that adding PAM to the original soil can reduce the plasticity value by 22,27% and increase the bearing capacity by 21,0% and 29,2% in unsoaked and soaked condition. According to the findings of this study, the role of PAM can increase the bearing capacity of the original soil, causing the soil to become embankment material.